THE EFFECT OF THE OPERATING MODES OF THE WELDING SOURCE ON THE HARDNESS OF THE DEPOSITED METAL - Швець, Олексій (SWorldJournal, 2025)
The present paper sets forth the findings of research conducted into the effect of welding power source operating modes (welding modes) on the hardness of deposited metal. The research study examined three distinct power source operating modes: The follow